Studi kasus: Analisis Kinerja Usaha Budidaya Ikan Lele dengan Semi-automatic Feeder - Diatin, Iis; Haq, Indah Dauna Syavira; Vinasyiam, Apriana (Universitas Batangahari Jambi, 2024)
The increasing trend in catfish production is accompanied by an increase in feed requirements and prices. This will result in the high cost of catfish production. One of the savings solutions can be done by reducing labour costs with the use of semi-automatic feeders. This study aims to analyse labour productivity in feeding methods using semi-automatic feeders and manual feeding in catfish rearing. The treatments in this study were manual feeding pond (A) and semi-automatic feeder pond (B), each with 3 replicates. Catfish with a weight of 3.4 ± 0.82 g and length of 7.8 ± 0.65 cm were reared in a pond measuring 8 m x 12 m x 0.65 m with a stocking density of 481 fish/m3. During 83 days of rearing, the fish were fed three times a day. The feeder machine sprayed feed at a speed of 16 g/sec. Growth data were taken five times in 83 days of rearing. The results showed that the parameters of survival rate (TKH), absolute growth rate of length (LPMP), and absolute growth rate of weight (LPMB) had a significant effect, while the amount of feed consumption (JKP), feed conversion ratio (RKP), and total harvest showed no difference in catfish farming. Based on labour productivity indicators, catfish farming with semi-automatic feeders has higher productivity